Thermal performance evaluation of boiling cooling system for the high-rate large-format lithium-ion battery under coolant starvations. (15th November 2022) - Wu, Nan; Chen, Yisheng; Lin, Boshen; Li, Junjie; Zhou, Xuelong
Abstract: The boiling cooling system exhibits superior cooling capacity and temperature homogenization ability, which has great potential in managing the undesirable temperature spike and temperature gradient of the large-format lithium-ion batteries. However, in-depth experimental investigation to reveal the effects of harsh operation conditions and parameters on the cooling characteristics are still lacking. In this study, thermal control ability of the boiling cooling system using Novec 7000 as coolant is evaluated for a large-format 20-Ah lithium-ion battery, with special attentions to the cooling performance under harsh operation conditions such as high-rate cyclic and coolant starvation. The experimental results show that the boiling-cooling system with uninterrupted/small coolant flow exhibits superior cooling capacity and the battery temperature can be controlled around 35 ± 2 °C over the high-rate cycles. However, when the coolant starvation issue occurs in the static mode, the maximum temperature and temperature difference rise drastically up to 53.45 °C and 18.56 °C in the fourth discharge process, which are abnormally higher than the system without injecting liquid coolant. The incorporation of 20PPI copper foam filler can alleviate the coolant starvation issue to some extent, which reduces the peak values of battery temperature and temperature difference by 13.28 % and 39.33 % under the same condition. Highlights: A boiling-cooling system for large-format pouch cells is evaluated under harsh conditions. The flow mode always affords stable and excellent cooling performance. The battery temperature is controlled around 35 ± 2 °C over the high-rate cycles. Coolant starvation causes abnormally high temperature and temperature gradient. Copper foam filler can alleviate the coolant starvation issue.